2007
DOI: 10.2307/25148790
|View full text |Cite
|
Sign up to set email alerts
|

On the Assessment of the Strategic Value of Information Technologies: Conceptual and Analytical Approaches

Abstract: This study compares two conceptual (resource-centered and contingency-based) and two analytical (linear and nonlinear) approaches that can be used to assess the strategic value of information technology. Two hypotheses related to these approaches are developed and tested based on matched survey data collected from the CEOs and CIOs of 110 firms. The results indicate that the resource-centered and contingencybased approaches provide complementary understanding of 1 Ritu Agarwal was the accepting senior editor f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
151
1
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 308 publications
(168 citation statements)
references
References 97 publications
0
151
1
3
Order By: Relevance
“…The effects of alignment has been empirically examined by previous studies M a n u s c r i p t 8 which found that alignment affects performance in general (Chan et al 1997;Choe 2007;Geissler et al 2001;Kearns and Lederer 2004;Oh and Pinsonneault 2007), and in critical areas such as sales growth and innovation (Chan et al 1997;Croteau and Bergeron 2001).…”
Section: Strategic It Alignment Perspective and It Strategiesmentioning
confidence: 99%
“…The effects of alignment has been empirically examined by previous studies M a n u s c r i p t 8 which found that alignment affects performance in general (Chan et al 1997;Choe 2007;Geissler et al 2001;Kearns and Lederer 2004;Oh and Pinsonneault 2007), and in critical areas such as sales growth and innovation (Chan et al 1997;Croteau and Bergeron 2001).…”
Section: Strategic It Alignment Perspective and It Strategiesmentioning
confidence: 99%
“…Other studies show that ICT directly facilitates the exploratory and exploitative activities of individuals (Kane and Alavi, 2007;Mom, Van den Bosch, and Volderba, 2003). Further studies show that ICT may serve exploratory goals like product innovation and exploitative goals such as cost reduction (Aral and Weill, 2007;Oh and Pinsonneault, 2007). These studies also emphasize that ICT is not a homogenous technology but rather that different types of ICT support different organizational architectures, employee activities, and performance dimensions.…”
Section: Technological Ambidexteritymentioning
confidence: 94%
“…To be more specific, business-IT alignment refers to "the degree to which the mission, objectives, and plans contained in the business strategy are shared and supported by the Information Technology (IT) strategy" (Reich & Benbasat, 1996, p. 56). The alignment framework inspired several empirical studies with findings that indicate that well-aligned organizations see their performance increases (Chan et al, 1997;Croteau & Bergeron, 2001;Sabherwal & Chan, 2001;Bergeron et al, 2004;Oh & Pinsonneault, 2007;Yayla & Hu, 2012;Gerow et al, 2014;Coltman et al, 2015). Research on business-IT alignment distinguishes between alignment in terms of intended strategic plans (e.g.…”
Section: Social Bi-alignment Approach For Open Source Ephr-based Servmentioning
confidence: 99%